Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract